2008
DOI: 10.1007/s12094-008-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

Uveal vs. cutaneous melanoma. Origins and causes of the differences

Carolina Belmar-Lopez,
Pablo Mancheno-Corvo,
Maria Antonia Saornil
et al.

Abstract: Melanoma is a malignant tumour derived from melanocytes (dendritic cells originated from the neural crest and capable to produce melanin synthesis) that could be established on the skin or less frequently on the uvea. The cellular origin from both kind of melanoma seems to be the same but the melanocytes migrates to the epithelia for cutaneous melanoma, while for uveal melanoma, they migrate to mesodermic tissues. Despite the common origin, both melanomas show extreme differences in their metastatic potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
1
17
1
Order By: Relevance
“…However, the reported assessment of the sensitivity and specificity of this test is controversial, because their cohort was not representative of the general primary melanoma patient population [10, 18]. Our results are not comparable with the results reported by Onken et al [20], because they studied uveal melanoma, which is different from skin cutaneous melanoma [85]. …”
Section: Discussioncontrasting
confidence: 87%
“…However, the reported assessment of the sensitivity and specificity of this test is controversial, because their cohort was not representative of the general primary melanoma patient population [10, 18]. Our results are not comparable with the results reported by Onken et al [20], because they studied uveal melanoma, which is different from skin cutaneous melanoma [85]. …”
Section: Discussioncontrasting
confidence: 87%
“…JARID1B has even been shown to be overexpressed in cutaneous melanoma in two additional studies, 42,43 as well as in several other malignancies. 24,[44][45][46] For instance, JARID1B has been found to be upregulated in many breast cancer cell lines and tumors, which suggests that JARID1B has tumor promoting activities. 45,46 Similarly, JARID1B is overexpressed in bladder and lung tumors and stimulates the proliferation of respective tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…24,[44][45][46] For instance, JARID1B has been found to be upregulated in many breast cancer cell lines and tumors, which suggests that JARID1B has tumor promoting activities. 45,46 Similarly, JARID1B is overexpressed in bladder and lung tumors and stimulates the proliferation of respective tumor cells. 42 Using both in vitro and in vivo models, Roesch et al found that JARID1B expression in malignant melanoma has been shown to have immediate antiproliferative effects, but later has a role in continuous tumor growth and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Although both uveal and cutaneous melanoma are of neural crest origin, and derived from melanocyte or their precursors, melanoblasts, they migrate to very different tissues and reside in very different micro‐environmental milieu (for review, Belmar‐Lopez et al., 2008). Uveal melanomas develop characteristic chromosomal abnormalities, such as loss of chromosome 3, abnormalities in chromosome 6 and, less frequently, gains in chromosome 8q.…”
Section: Immunological Considerations Distinguishing Cutaneous and Uvmentioning
confidence: 99%